Analysis of Total Quality Management in Balenggek Tokok Chicken Business - Salasabila Putri, Nada; Oktafiani, Salsabilla; Acyar Septiano, Tyo; Helmi Habibie, Mar’ie; Mulyawan Harahap, Agung Satria (Pt. Threeple Herphi Educate, 2024)
Technological advances have created new challenges in the management of goods and services, which require special attention to management and quality control. This study evaluates the implementation of Total Quality Management (TQM) at Ayam Tokok Balenggek business with the aim of increasing customer loyalty. A qualitative approach was used in this study, through interviews, observations, and closed questionnaires, to analyze TQM implementation and identify problems using Fishbone Diagram. The results showed that TQM at Ayam Tokok Balenggek includes quality management of fresh raw materials, cleanliness of the dining area, and equipment used. However, some shortcomings were found, such as narrow and hot eating areas, lack of fan facilities, and limitations in the provision of certain chicken parts. The analysis also revealed that TQM implementation is supported by five servqual indicators, namely: Reliability, Responsiveness, Assurance, Empathy, and Physical Evidence. These findings confirm the importance of effective TQM implementation to improve service quality and customer satisfaction, which in turn can increase business competitiveness in the market.